2017
DOI: 10.1590/0101-60830000000118
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma brain metastases presenting as delirium: a case report

Abstract: Background: Metastatic tumours sometimes present with neuropsychiatric symptoms, however psychiatric symptoms as rarely the first clinical manifestation. Cutaneous melanoma is the third most common cause of brain metastasis, with known risk factors increasing the chance of such central nervous system metastization. Objectives: We present a clinical report of delirium as the first clinical manifestation of melanoma brain metastases, illustrating the relevance of an adequate and early differential diagnosis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…The patient had a history of drug addiction, presenting psychomotor agitation and aggressive behavior, as can be observed in many cerebral neoplasms [ 54 , 55 , 56 , 57 ]. Morais described a case of delirium in a patient with brain melanoma metastases [ 58 ] and other authors reported headache and diplopia in a 27-year-old man affected by primary meningeal melanocytoma in the anterior cranial fossa [ 59 ]. However, we can ascribe the first presented symptoms (headache and vomit) to increased intracranial pressure, probably due to the increased neoplastic mass in the posterior fossa and a subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had a history of drug addiction, presenting psychomotor agitation and aggressive behavior, as can be observed in many cerebral neoplasms [ 54 , 55 , 56 , 57 ]. Morais described a case of delirium in a patient with brain melanoma metastases [ 58 ] and other authors reported headache and diplopia in a 27-year-old man affected by primary meningeal melanocytoma in the anterior cranial fossa [ 59 ]. However, we can ascribe the first presented symptoms (headache and vomit) to increased intracranial pressure, probably due to the increased neoplastic mass in the posterior fossa and a subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Em fases ini ciais, quadros de delirium hipoativo podem ser interpretados como depressão. Em situações raras, o delirium pode ser a manifestação inicial de lesões neoplásicas no SNC 15 . A abordagem do delirium compreende de início a identificação e a correção, sempre que possível, de causas subjacentes (vide Quadro 2).…”
Section: Deliriumunclassified